Intrauterine upper limb thrombosis: an unusual presentation - Bhaisara, Baraturam B.; Korday, Charusheela S.; Wade, Minal R.; Yaragatti, Vikram V.; Bhatawdekar, Anjali M.; Mauskar, Anupama V. (International Journal of Contemporary Pediatrics, 2019)
Intrauterine thrombosis with extremity ischemia presenting at birth in a newborn is a rare event. A 29 year old mother, 2nd gravida with one first trimester spontaneous abortion delivered a 33week gestation male preterm baby. On Examination, the entire left upper limb was ischemic and edematous with an absent flow on Doppler USG. Low molecular weight heparin (LMWH) was started after which gradually the limb turned pink with good volume pulsations. Thrombophilia mutation studies revealed the heterozygous state for the MTHFR (C677T) mutation only in the mother. Prompt diagnosis and early treatment has a favourable outcome in cases of intra-uterine thrombo-embolism.